EOS789, pan‐phosphate transporter inhibitor, ameliorates the progression of kidney injury in anti‐GBM‐induced glomerulonephritis rats - Yoshinori Tsuboi; Yasuhiro Ichida; Atsuko Murai; Akira Maeda; Manami Iida; Atsuhiko Kato; Shuichi Ohtomo; Naoshi Horiba (Pharmacology Research & Perspectives, 2022)
Abstract Hyperphosphatemia associated with chronic kidney disease (CKD) not only dysregulates mineral metabolism and bone diseases, but also strongly contributes to the progression of kidney disease itself. We have identified a novel drug for hyperphosphatemia, EOS789, that interacts with several sodium‐dependent phosphate transporters (NaPi‐IIb, PiT‐1, and PiT‐2) known to contribute to intestinal phosphate absorption. In this study, we investigated whether EOS789 could ameliorate kidney disease progression in glomerulonephritis rats. Anti‐glomerular basement membrane (GBM) nephritis was induced in rats by intravenously administering two types of anti‐rat GBM antibodies. We evaluated the effect of EOS789 administered in food admixture on hyperphosphatemia and kidney disease progression. In an anti‐GBM nephritis rats, which exhibit a significant increase in serum phosphate and a decline in renal function, EOS789 dose‐dependently improved hyperphosphatemia and EOS789 at 0.3% food admixture significantly ameliorated kidney dysfunction as shown in the decline of serum creatinine and BUN. Renal histopathology analysis showed that EOS789 significantly decreased crescent formation in glomeruli. To elucidate the mechanism underlying glomerular disease progression, human mesangial cells were used. High phosphate concentration in media significantly increased the expression of Collagen 1A1, 3A1, and αSMA mRNA in human mesangial cells and EOS789 dose‐dependently suppressed these fibrotic markers. These results indicate that EOS789 prevented glomerular crescent formation caused by mesangial fibrosis by ameliorating hyperphosphatemia. In conclusion, EOS789 would not only be useful against hyperphosphatemia but may also have the potential to relieve mesangial proliferative glomerulonephritis with crescent formation.